Comunicação Empresarial e Mercado Cultural: observações de um educador - Cardoso, Claudio (Organicom, 2006)
Expressions as marketing promotion, economy of the culture, and cultural marketing still excite preconceptions that must be analysed (maybe surpassed) so that new producers of art & culture could freely develop new patterns that enhance cultural development and wealth. The notes here gathered intend to serve as an incentive to new producers in art & culture, and to encourage them towards a future of great perspectives.